Mobilização articular e compressão isquêmica sobre os pontos gatilhos miofasciais do músculo trapézio superior em sujeitos com tendinopatia do manguito rotador: ensaio clínico randomizado simples cego - Silva, Alyssa Conte da (2021)
Introduction: Subjects with Rotator Cuff Tendinopathy (RCT) present pain and hyperactivation in the upper trapezius muscle, predisposing to the occurrence of Myofascial Trigger Points (MTrPs). One of the techniques used to promote the deactivation of these points is the ischemic compression technique. However, it is relevant to gather what is scientific evidence for the use of this technique in subjects with shoulder pain. In addition, joint mobilization techniques provide positive results for shoulder pain, but usually immediately after application or in the short term. It is estimated that the techniques of joint mobilization when applied together with the ischemic compression technique can enhance its effects. Objective: Gather scientific evidence of the ischemic compression technique (CI) on pain and function in individuals with shoulder pain and investigate the clinical effects of the ischemic compression technique on the upper trapezius muscle MTrPs in association with joint mobilizations on pain and shoulder function in subjects with RCT.Thus, two studies were carried out: Study I: The effectiveness of ischemic compression technique on Ppain and function in individuals with shoulder pain: a systematic review; Study II: Clinical efficacy of the association of joint mobilizations with the ischemic compression technique in subjects with rotator cuff related shoulder pain: a single blind randomized clinical trial. Methods: In study I, the systematic review was performed on the PubMed, CINAHL, SPORTDiscus, PEDro and Web of Science databases and the methodological quality of the studies was assessed using the PEDro scale. In study II, 60 individuals with Rotator Cuff Related Shoulder Pain (RCRSP) were evaluated, divided into 3 groups: Mobilization Group (MG = 20), Compression Group (CG = 20) and Placebo Group (PG, n = 20). All participants received intervention twice a week and were evaluated pre-intervention, after 6 weeks of treatment and after 1 month (follow-up). The variables evaluated were pain (VAS), function (DASH questionnaire), psychological factors (Tampa questionnaires and pain catastrophization), perceived global change (GROC), shoulder abduction ROM (inclinometer), pressure pain threshold (algometer) and characteristics of MTrPs (ultrasound-US). The ANOVA Two Way test with Bonferroni post hoc was applied, considering a significance level of 5%. Results: In study I, the search resulted in 572 studies, of which 5 were included for analysis. Methodological quality ranged from 4 points (reasonable) to 9 points (excellent). Pain was assessed by all studies while function was assessed by 3, showing that the IC technique produces immediate and short-term positive effects on pain and short-term positive effects on shoulder function in individuals with shoulder pain. In study II, the three groups showed improvements, with time interaction for the variables pain, function, pain catastrophization, while the area of the MTrPs was significant only in the CG, reaching the minimum detectable change. Conclusion: The results showed that the ischemic compression technique produced short-term pain and shoulder function. Additionally, the ischemic compression technique produced an effect in the area of MTrPs, when associated with joint mobilizations in subjects with RCRSP.